THE INFLUENCE OF THE SOCIODRAMA METHOD ON STUDENTS 'SPEAKING SKILLS - Salma Halidu; Gamaria Minti (International Journal of Innovations in Engineering Research and Technology, 2020)
The purpose of this study was to determine the effect of the sociodrama method on the speaking skills of fifth grade students of SD Negeri 2 Bulango Timur, Bone Bolango Regency. The model used in this research is a quantitative approach to the experimental method with a one group pretest-posttest design . The data collection techniques used in this study were tests (pretest and posttest ), while observation and documentation were the supports. The sample of this research was 19 students of grade V. The results of the acquisition of an average pretest score of 10.40 and an average posttest score of 1,300. The results of this study are reinforced by the results of the t test which states that t arithmetic > t tablenamely 7.17> 2.10 at the 0.05 level. So that H 0 is rejected and H a is accepted . In this case it can be concluded that the results of this study indicate that there is an influence of the sociodrama method on the speaking skills of fifth grade students of SD Negeri 2 Bulango Timur, Bone Bolango Regency.